Analisis Kebutuhan Tenaga Perawat Unit Pelayanan Intensif Berdasarkan Beban Kerja dan Kompetensi di Unit Pelayanan Intensif Rumah Sakit Dr Oen Solo Baru Tahun 2015 - Gunawan, Antonny Halim (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2016)
Nurses, as human resources for health also contribute greatly to the health services in hospitals and to provide services directly to patients. Nursing services at Intensive Care Unit has to be developed along with the technology development. Therefore, there is a need to concern the effieciency of nurses in term of quantity and competencies. This research discussed about the needs analysis nursing staff in the Intensive Care Unit of dr. Oen Solo Baru Hospital based on workload (using time and motion technique to 7 nurses then processed by Ilyas Methods) and work competencies based on Aditama 2007 and Ilyas (depth interview to three informants with a focus on job knowledge, skills and attitudes). Results of this research show that productive time amounted to 81.56%, the lack of standards and competencies, and it need 51 nurses.